(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Leukoencephalitis is a neurological disorder characterized by inflammation of the white matter of the brain. It can result from a range of causes, such as viral infections, autoimmune disorders, and metabolic diseases. In children, this condition can lead to a variety of neurological symptoms, ranging from mild cognitive impairment to severe motor dysfunction. The critical challenge for clinicians is to identify the underlying cause promptly, as the prognosis and treatment plans vary significantly based on the etiology. This article delves into the causes, diagnostic methods, and treatment strategies for managing leukoencephalitis in pediatric patients.